Frequency of attention deficit hyperactivity disorder in university students studying medicine in Paraguay - Dávalos-Ortiz, José C. (2025)
Introduction: Attention-Deficit/Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterized by the persistent presence of inattention, hyperactivity, or impulsivity. This disorder negatively impacts the individual, educational, social, and family development of those affected. Objective: To determine the frequency of ADHD among Medical students at the Universidad Autónoma San Sebastián (UASS) during 2024. Methodology: An observational, descriptive study with an analytical component, cross-sectional in design, was conducted using non-probabilistic consecutive sampling. Medical students at UASS aged 18 years or older who consented to participate were included. The Adult ADHD Self-Report Scale V1.1 (ASRS-V1.1) Screening Questionnaire was used for the identification of ADHD symptoms. Results: The study included 144 participants, with a mean age of 26.2±7.2 years (range: 18-54); 91 (63.2%) of the students were female. The average score on the questionnaire was 3.2±1.7 points, resulting in an ADHD frequency of 64 (44.4%). No statistically significant association was found between the presence of ADHD symptoms and sex (χ2=2.509; p=0.113) or age (U=2550; p=0.969). Conclusion: The frequency of ADHD among Medical students at UASS (San Lorenzo, Paraguay) was notably high.